2020
DOI: 10.1007/s11116-020-10080-5
|View full text |Cite
|
Sign up to set email alerts
|

What drives the gap? Applying the Blinder–Oaxaca decomposition method to examine generational differences in transportation-related attitudes

Abstract: Considerable recent work suggests that Millennials' behaviors may be converging with those of Generation X as they enter later life stages, but few have investigated whether attitudes, which are often strong predictors of behavior, are undergoing the same convergence. In this study, we analyze the existing generational gap in four transportation-related attitudes (currently pro-urban, long-term pro-urban, pro-car ownership, and pro-environment), and examine the differential effects of other characteristics, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 46 publications
1
22
0
Order By: Relevance
“…, The interaction term, which explains how differences in the coefficients (i.e., how health affects disability) differ across the distribution of values for the endowments (i.e., health differences), is relatively small in magnitude, implying that it does not factor into our interpretation of the results. This small interaction term suggests that the magnitude of the endowment effect does not differ between groups, or equivalently the magnitude of the coefficient effect does not differ between groups (Etezady et al 2020).…”
Section: Resultsmentioning
confidence: 92%
“…, The interaction term, which explains how differences in the coefficients (i.e., how health affects disability) differ across the distribution of values for the endowments (i.e., health differences), is relatively small in magnitude, implying that it does not factor into our interpretation of the results. This small interaction term suggests that the magnitude of the endowment effect does not differ between groups, or equivalently the magnitude of the coefficient effect does not differ between groups (Etezady et al 2020).…”
Section: Resultsmentioning
confidence: 92%
“…At the same time, there are many works that study the value orientations of the already present generational cohorts in different countries. From this point of view, the most interesting works are by Noble and Schewe (2003), Hung et al (2007), Stewart et al (2017), Martínez-Buelvas and Jaramillo-Naranjo (2019), and Etezady et al (2020).…”
Section: Methods For Determining the Time Range Of Generationsmentioning
confidence: 99%
“…The indicators of differences between cohorts are directly analyzed based on the analysis of the respondents' consistency, correlation, and one-sided analysis of variance (ANOVA). Etezady et al (2020) explore the differences between generations in the United States by four indicators, using the Blinder-Oaxaca decomposition method. However, they also consider the predefined time ranges of generations.…”
Section: Methods For Determining the Time Range Of Generationsmentioning
confidence: 99%
“…More recent studies, however, suggest that mode choice in older adults is more diversified, and usually depends on travel purposes. Moreover, older adults show more openness toward shifting modes than seniors from previous generations (33,34). Specific factors that influence travel mode use and travel mode shift for food shopping purposes include loss of mobility, weather conditions, and the need to carry packages.…”
Section: Understanding Mode Shift In Older Adultsmentioning
confidence: 99%
“…Motives for Walking or Cycling (n = 16). Active travel modes had been used once or more for grocery shopping by 50.8% of the sample participants over the previous month, whereas 34.4% reported that they really wanted to use this mode for each grocery trip (see Table 1). Walking or cycling to the grocery store was associated with many individual benefits such as feelings of satisfaction and autonomy, additional physical exercise gained from walking to stores and the pleasure of conducting a social activity outside the home.…”
Section: Underlying Motivesmentioning
confidence: 99%